The Relationship between Knowledge and Attitudes and COVID-19 Prevention Behavior in Pregnant Women in Makassar - Fitriani, Rini (Jurnal Midwifery, 2025)
Introduction coronavirus is a new virus that shocked the world in early December 2019. The rapid spread and increasing cases can cause pregnant women with COVID-19 at risk for miscarriage, fetal distress, premature labor, premature rupture of membranes, and growth disorders. Based on data on cases of COVID-19 incidence, Indonesia is the country with the highest daily cases in the world, beating Brazil and India The purpose of this study was to determine the relationship of knowledge and attitudes with COVID-19 prevention behavior in pregnant women in Makassar. Method this study used a cross-sectional design with a purposive sampling technique. The research subjects were pregnant women totaling 144 respondents. Bivariate data analysis used the Person Chi-Square test. Result of statistical analysis are that knowledge is significantly related to attitudes with a P value of 0.025 <0.05, and knowledge is not significantly related to behavior with a p value of 0.598 > 0.05. Conclusion Pregnant women should increase their knowledge about the prevention of COVID-19 infection and be able to apply it in the form of behavior in everyday life